Number 15 (August 1984) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1984)
A Report on the Fishes of Bull Mountain Creek, with Comments on the Status of Rare Species. By M. Pierson and C.A. Schultz, 3 pp. Fishes of the Middle Fork of the Kentucky River, Kentucky. By B.A. Branson and D.L. Batch, 7 pp. A Survey of Fish Communities of Streams in Coal Surface Mining Areas of the Cumberland Plateau, Tennessee. By C.J. O'Bara and R.D. Estes, 4 pp. Recent Collections of Fishes from the Big South Fork of the Cumberland River System, Tennessee and Kentucky. By C.J. O'Bara and R.D. Estes, 5 pp.
Keywords: fishes; bull mountain creek; middle fork; kentucky river; coal surface mining; cumberland plateau; tennessee; big south fork; cumberland river system; kentucky